СХЕМА АРКАДІЄВА-МАРКСА З РЕЗОНАНСНИМ ЗАРЯДОМ ЄМНІСНИХ НАКОПИЧУВАЧІВ ЕНЕРГІЇ В МАГНІТНО-ІМПУЛЬСНИХ УСТАНОВКАХ - Батигін, Ю.В.; Шиндерук, С.О.; Чаплигін, Е.О.; Фендриков, Д.В. (Інститут електродинаміки НАН України, Київ, 2024)
The effective use of Arkadiev-Marx scheme with a resonant charging of capacitive storages in magnetic-pulse installations, as power sources, in technologies using the electromagnetic field energy is proposed and substantiated. It is found that during charging the maximum voltage amplitude at capacitor increases by number times equal to the quality factor of the charging circuit at the fundamental frequency of the harmonic expansion of exciting signal, but by ~34% less than possible maximum. The calculations of the characteristics of magnetic-pulse complex intended for the repair of damaged car bodies show the high efficiency of using the Arkadiev-Marx circuit with the resonant charging of capacitive storage. It is found that during the time of ~0.45 s the battery of 10 capacitors connected in parallel with total capacitance of ~100 μF can be charged up to voltage of ~7500 V with stored energy of ~2.8 kJ. The results of the work allow us to give recommendations on the practical increase in the efficiency of magnetic-pulse metal processing. References 16, figures 4.